PEER VICTIMIZATION AND AGGRESSION AMONG SCHOOL STUDENTS - R, Pushpalatha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Research around the world has shown that peer victimization is a common phenomenon among pupils in educational institutions. Peer victimization here refers to different forms of repeated physical or emotional harm directed towards a child. Physical harm could include hitting or punching, whereas emotional harm could include name-calling or being excluded from the peer group. Aggression is defined as a behaviour directed toward the goal of harming or injuring another living being, where the other person will be motivated to avoid the harm. Aggression is related to mental health problems in children, including externalizing disorders as Oppositional Defiant Disorder and Conduct Disorder, as well as internalizing problems with Depression and Anxiety. The belief that aggression is more of a problem of the industrialized nations is falling short of space as the developing ones are catching up with them. Aggression not only spoils the school environment but also is a risk factor for future delinquency (UNESCO). The aim is to study peer victimization and aggression among school children. The sample consisted of 60 children of which 30 were boys and 30 were girls. The age of the students ranged between 10 to 16 years. All the students were residents of Bangalore city. The students were administered the multidimensional peer victimization scale-24 and the aggression scale. Prior consent from the school and parents was taken before administering the scales to children. The subjects were assured regarding the confidentiality of the data and that the collected data would be used for research purposes only. A purposive sampling design was opted for the study. The mean, SD and t were computed using appropriate statistical measure. The result showed that there was a significant gender difference in peer victimization and aggression